Muslim Youth Religiosity: in Terms of Gender Differences and Educational Environment - Warsiyah Warsiyah (Universitas Islam Negeri (UIN), 2018)
Abstract This study aims to determine differences in the religiosity of Muslim adolescents regarding differences in the educational environment and gender. Data analysis was performed by the score collected by questionnaire, which was developed to measure the level of adolescent religiosity consisting of four dimensions: faith, intellectual, ritual and social. The study involved 97 Muslim teenagers taken random cluster sampling from an affordable population of students studying at SMA N and MA in Simo district Boyolali district. The results showed that subject scores varied and were above the theoretical averages, indicating that Muslim youth in Simo had a high degree of religiosity. The result of t-test analysis shows that there is a difference of religiosity level between adolescents studying in heterogeneous and homogenous institutions. The value of t-count is 2,668 bigger than t criterion (t-Table = 2.010) at 5% significance level. Abstrak Penelitian ini bertujuan untuk mengetahui perbedaan dalam religiusitas remaja Muslim dalam hal perbedaan di lingkungan pendidikan dan jenis kelamin. Analisis data dilakukan berdasarkan skor yang dikumpulkan melalui kuesioner, yang dikembangkan untuk mengukur tingkat religiusitas remaja yang terdiri dari empat dimensi: iman, intelektual, ritual dan sosial. Penelitian ini melibatkan 97 remaja Muslim yang diambil melalui tehnik sampel gugus (cluster random sampling) dari populasi siswa yang belajar di Sekolah Menengah Atas Negeri dan Madrasah Aliyah di Kecamatan Simo, Kabupaten Boyolali. Hasil penelitian menunjukkan bahwa skor subjek bervariasi dan berada di atas rata-rata teoritis, menunjukkan bahwa pemuda Muslim di Simo memiliki tingkat religiusitas yang tinggi. Hasil analisis uji-t menunjukkan bahwa ada perbedaan tingkat religiusitas antara remaja yang belajar di lembaga-lembaga yang heterogen dan remaja yang belajar di lembaga-lembaga yang homogen. Nilai t-count adalah 2.668 lebih besar dari kriteria t (t-Tabel = 2.010) pada tingkat signifikansi 5%. How to Cite : Warsiyah. (2018).  Muslim Youth Religiosity: With the References of Gender Differences and Educational Environment. TARBIYA: Journal of Education in Muslim Society, 5(1), 19-29. doi:10.15408/tjems.v5i1.7842.